Pengaruh Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Bekasi Barat - Ismail Noto Wijoyo; Martinus Wahyu Purnomo (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
In developing more advanced human resources it is very important, proper employee management can realize human resources or improve the performance of skilled workers and help agencies achieve their goals. West Bekasi District is one of the state administrative bodies responsible for coordinating government administration, serving and empowering the surrounding community. There are several problems, namely a lack of supervision from the leadership, so that there are still employees who arrive late and do not come in without explanation and the facilities provided are inadequate so that employee performance is still less than optimal. This research aims to examine the influence of leadership and work environment on employee performance, both partially and simultaneously. The research method used was a quantitative method with a sample of 37 respondents from the West Bekasi District Office. Data collection techniques were carried out through interviews, observation and questionnaires. Data processing uses SPSS 22 to carry out multiple linear regression tests and hypothesis testing. The results of this research show that partially or simultaneously leadership and the work environment have a positive effect on employee performance.